Research progress in the construction of animal models of autoimmune thyroiditis - Ke Liu; Pei Zhang; Ling Zhou; Lin Han; Linhua Zhao; Xiaotong Yu (Taylor & Francis Group, 2024)
AbstractAutoimmune thyroiditis (AIT), also known as Hashimoto's thyroiditis (HT), is an autoimmune disease that is characterised by elevated thyroid-specific antibody titres. The incidence of AIT is increasing year over year, making it urgent to establish a suitable animal model for this condition, in order to better explore its pathogenesis and potential pharmaceutical mechanisms for treatment. Owing to a lack of basic research on this disease, problems such as disparate modelling methods with unclear and varying success rates make it difficult for researchers to obtain effective information on AIT in the short term. This report summarises and analyzes the current literature on AIT and combines actual operability to explain the selection and specific implementation processes behind the uses of different modelling approaches, to provide a better overall understanding of autoimmune thyroid diseases.